Super-rigid affine Fano varieties. (17th November 2018) - Cheltsov, Ivan; Dubouloz, Adrien; Park, Jihun
Abstract : We study a wide class of affine varieties, which we call affine Fano varieties. By analogy with birationally super-rigid Fano varieties, we define super-rigidity for affine Fano varieties, and provide many examples and non-examples of super-rigid affine Fano varieties.